Sovereign Credit Rating Announcements and Baltic Stock Markets - Klimavičienė, Asta (Organizations and Markets in Emerging Economies, 2011)
This study examines whether sovereign credit rating announcements convey price relevant information to investors in Baltic stock markets, and tests the degree of anticipation and price reaction. Event study methodology is employed to test for the price impact of sovereign credit rating announcements by Moody’s, S&P, and Fitch. This enables to analyse whether there is an anticipation of the forthcoming announcement in a particular market, a price impact on the announcement day, and a possible delayed reaction. Results indicate that there is an asymmetric reaction: the price impact of negative events is several times larger than that of positive events. Moreover, although some types of rating announcements are anticipated, there is still a significant price impact on the announcement day. The impact differs across the three Baltic stock markets, and depends on the credit rating agency issuing the announcement. The main conclusion is that sovereign credit rating announcements contain pricing relevant news in addition to information already in a public domain.
Keywords: OMX Baltic stock markets; sovereign credit ratings; event study